Characteristics of Nests and Nest Trees of the Bornean Orangutan Subspecies (Pongo pygmaeus wurmbii, TIEDEMAN 1808) in the Protected Area of Rungau River Riparian Zone, Central Kalimantan Province - Firmansyah Firmansyah; Achmad Yanuar; Tatang Mitra Setia (Universitas Nasional Jakarta, 2023)
Orangutan conservation efforts can be carried out through habitat management both within and outside of conservation areas. The protected areas along the Rungau River has indications of an orangutan population. So, it is necessary to study the characteristics of nests and nest trees. The research method uses transect lines to record the characteristics of the nets and the characteristic of the nest tree. Based on research on the characteristics of the nest, it is known that the height of the nest ranges from 5 to 32 m from the ground. Class B is the dominant nest class. Dominant nest diameter of more than 1 m. Then the characteristics of the nest tree are known that the height of the nest tree ranges from 10 to 37 m. In adults, tree nests have a diameter at breast hight in the range of 5 to 96 cm. The dominant type of nest tree species are guava and meranti.